Pest and Disease Control Training for Women’s Urban Farming Group in Semarang, Indonesia - Indriyanti, Dyah Rini; Widiyaningrum, Priyantini; Dewi, Pramesti; Elawati, Nunung Eni; Yati, Ernallah; Melinda, Aura Tirsa; Ananda, Rahimma Artantia; Puspita, Maria Ayu (Universitas Negeri Semarang, 2024)
The Women Farmers Group in Sampangan, Semarang, Indonesia has managed an urban farming area since 2018, cultivating vegetables, fruits, and medicinal plants. However, they face persistent challenges in controlling plant pests and diseases due to limited knowledge. This community service aimed to enhance their understanding through structured training on sustainable pest and disease control in horticultural crops. The activity involved preparation, implementation, and evaluation phases, with participatory methods including pre-test and post-test evaluations, tutorials, and discussions. The training introduced eco-friendly techniques such as cultural, biological, and mechanical control. The participants showed high enthusiasm during the sessions. Results indicated a 25% increase in knowledge, demonstrating the effectiveness of the training. This program supports SDG 2 (Zero Hunger) and SDG 11 (Sustainable Cities and Communities) by promoting sustainable agriculture and empowering women in urban farming practices.